Pancreatic neuroendocrine tumor with complete replacement of the pancreas by serous cystic neoplasms in a patient with von Hippel-Lindau disease: a case report - Shimpei Maeda; Fuyuhiko Motoi; Shuhei Oana; Kyohei Ariake; Masamichi Mizuma; Takanori Morikawa; Hiroki Hayashi; Kei Nakagawa; Takashi Kamei; Takeshi Naitoh; Michiaki Unno (Surgical Case Reports)
Abstract Background von Hippel-Lindau disease is a dominantly inherited multi-system syndrome with neoplastic hallmarks. Pancreatic lesions associated with von Hippel-Lindau include serous cystic neoplasms, simple cysts, and neuroendocrine tumors. The combination of pancreatic neuroendocrine tumors and serous cystic neoplasms is relatively rare, and the surgical treatment of these lesions must consider both preservation of pancreatic function and oncological clearance. We report a patient with von Hippel-Lindau disease successfully treated with pancreas-sparing resection of a pancreatic neuroendocrine tumor where the pancreas had been completely replaced by serous cystic neoplasms, in which pancreatic function was preserved. Case presentation A 39-year-old female with von Hippel-Lindau disease was referred to our institution for treatment of a pancreatic neuroendocrine tumor. Abdominal computed tomography demonstrated a well-enhanced mass, 4 cm in diameter in the tail of the pancreas, and two multilocular tumors with several calcifications, 5 cm in diameter, in the head of the pancreas. There was complete replacement of the pancreas by multiple cystic lesions with diameters ranging from 1 to 3 cm. Magnetic resonance cholangiopancreatography showed innumerable cystic lesions on the whole pancreas and no detectable main pancreatic duct. Endoscopic ultrasound-guided fine-needle aspiration of the mass in the pancreatic tail showed characteristic features of a neuroendocrine tumor. A diagnosis of pancreatic neuroendocrine tumor in the tail of the pancreas and mixed-type serous cystic neoplasms replacing the whole pancreas was made and she underwent distal pancreatectomy while avoiding total pancreatectomy. The stump of the pancreas was sutured as firm as possible using a fish-mouth closure. The patient made a good recovery and was discharged on postoperative day 9. She is currently alive and well with no symptoms of endocrine or exocrine pancreatic insufficiency 8 months after surgery. Conclusions A pancreas-sparing resection should be considered for patients with pancreatic neuroendocrine tumors and complete cystic replacement of the pancreas to preserve quality of life after surgery.